ANALISIS KEBERADAAN DUA POPULASI PADA STELLAR HALO GALAKSI MENGGUNAKAN DATA GAIA DR2, GALAH DR2, RAVE DR5, DAN LAMOST DR4 v2 - Annisa, Nur
Stellar Halo is one of the Galactic components which has a spheroidal shaped surrounding the Galaxy. Even though containing 1% of the total stellar mass, stellar halo is an important component for understanding formation history and the evolution of the Galaxy. The oldest and metal-poor stars are suspected found on stellar halo. Its metallicity and orbital motion provide nature information of first stars in the universe. Previously, stellar halo was considered to be composed of only one population. Carollo et al. (2007,2010) concluded the existence of a dual stellar halo (inner and outer halo) which has a different characteristic, but there is still debate from other scientists. Therefore in this final project using the newest astrometry survey, Data Release Two of The Gaia satellite mission (GDR2) which is combined with spectroscopic data sets from GALAH DR2, RAVE DR5, dan LAMOST DR4 v2 to examine and analyze the kinematics and structure of the Galactic stellar halo around the sun. Then fitting the data using Lavenberg-Marquardt method. The results for data set which has metallicity [Fe/H] < -1,6 and Zmax > 10 kpc best modeled by three populations. Outer halo with mean value of rotation velocity ???????????? = ?76 km/s and standard deviation of rotation velocity ???????????? = 168 km/s, inner halo with mean value of rotation velocity ???????????? = ?2 km/s and standard deviation of rotation velocity ???????????? = 36 km/s, and population which has kinematics like thick disk but its metallicity as poor as halo, this population is called metal weak thick disk (MWTD) with mean value of rotation velocity ???????????? = 131 km/s and standard deviation of rotation velocity ???????????? = 126 km/s.